Relationship between the anthropometric characteristics and physical fitness in wheelchair basketball players - Romarate, A.; Granados, C.; Iturricastillo, A.; Lizundia, M.; Yanci Irigoyen, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The three main objectives of this paper were, in first place, to describe the anthropometric characteristics and the physical conditions and in wheelchair basketball (WB) players, in second place, to analyze the relation between the anthropometric characteristics and the physical conditions, and in third place, to study the association between the different physical conditions. Eleven players (33,82 ± 10,17 years, 74,50 ± 5,18 cm sitting size) from the First Division of the Spanish WB League took part in this study. The anthropometric characteristics (body mass, skin folds and body perimeters and diameters), and physical condition (acceleration, change of direction, muscular strength and aerobic capacity) were measured. The obtained results shown an significant association between the summation of the folds and the time in the Pick-up test (r = -0,64±0,35 CL, p < 0,05), in the maximal pass test (Mpass) (r = 0,74;±0,28 CL, p < 0,01) and the test of the medicine ball throw (0,73;±0,29 CL, p < 0,05). The results obtained in the present study show that the anthropometric characteristics could be related to the change direction ability and muscle strength in WB players of national category (Spanish First division).